2019
DOI: 10.1186/s12879-019-3944-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of prophylaxis for Pneumocystis jirovecii pneumonia involving trimethoprim-sulfamethoxazole dose reduction in kidney transplantation

Abstract: Background Trimethoprim-sulfamethoxazole (TMP-SMX) is the drug of choice for anti- Pneumocystis jirovecii pneumonia (PcP) prophylaxis in kidney transplant recipients (KTR). Post-transplant management balances preventing PcP with managing TMP-SMX-related adverse effects. TMP-SMX dose reduction addresses adverse effects but its implications to incident PcP are unclear. Methods We performed a retrospective review of all patients transplanted betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Dermatologists frequently administrate TMP/SMX to patients with pemphigus, pemphigoid, dermatomyositis and systemic lupus erythematosus. Because we treat these patients with corticosteroids and/or immunosuppressants for a long period of time, adverse events often occur, so we often reduce the dose of TMP/SMX due to adverse events 3 . We have managed to use TMP/SMX without causing adverse events 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dermatologists frequently administrate TMP/SMX to patients with pemphigus, pemphigoid, dermatomyositis and systemic lupus erythematosus. Because we treat these patients with corticosteroids and/or immunosuppressants for a long period of time, adverse events often occur, so we often reduce the dose of TMP/SMX due to adverse events 3 . We have managed to use TMP/SMX without causing adverse events 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Because we treat these patients with corticosteroids and/or immunosuppressants for a long period of time, adverse events often occur, so we often reduce the dose of TMP/SMX due to adverse events. 3 We have managed to use TMP/SMX without causing adverse events. 4 A non-blind randomized controlled trial is now in progress.…”
mentioning
confidence: 99%
“…Prasad et al . [ 14 ] reported that SMX/TMP 400 mg/80 mg three times a week in renal transplant patients reduced AEs without affecting prophylaxis. Takenaka et al .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Despite primary PJP prophylaxis, many studies report PJP cases and outbreaks occurring after prophylaxis, with an incidence of 44.6-176 cases per 100 000 person-years. 5,12,[14][15][16][17][18][19][20][21][22][23][24][25] Transmission of PJP occurs by two primary modes: contact with PJP-infected patients or asymptomatic carriers and environmental exposure. 18,20,21,23,24 This can result in spread amongst immunocompromised patients within a renal transplant centre leading to a PJP outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…5,12,[14][15][16][17][18][19][20][21][22][23][24][25] Transmission of PJP occurs by two primary modes: contact with PJP-infected patients or asymptomatic carriers and environmental exposure. 18,20,21,23,24 This can result in spread amongst immunocompromised patients within a renal transplant centre leading to a PJP outbreak. 18,20,21,24 Universal prophylaxis has been used to manage such outbreaks, but evidence to guide the duration of prophylaxis is limited, leading to variability between transplant centres, ranging from 1 year after the last case to lifelong prophylaxis.…”
Section: Introductionmentioning
confidence: 99%